1981
DOI: 10.1007/bf00294930
|View full text |Cite
|
Sign up to set email alerts
|

Systematic growth studies, cocultivation, and cell hybridization studies of Werner syndrome cultured skin fibroblasts

Abstract: The growth of 20 independently derived skin fibroblastlike (FL) cell strains from three individuals with Werner syndrome (adult progeria) was compared with the growth of ten FL cell strains from normal individuals. Population growth rates and total replicative life spans of Werner syndrome strains averaged 53% and 27%, respectively, of the growth rates and life spans of non-Werner strains. In the first few passages, four Werner syndrome strains demonstrated population growth rates in the low normal range, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
47
0

Year Published

1985
1985
2004
2004

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(51 citation statements)
references
References 34 publications
4
47
0
Order By: Relevance
“…In mammalian cells, the duration of the S phase is almost always 8-10 hr. If all the cells in these young cultures were growing, this would imply a generation (intermitotic) time of between 1 and 4 days, which is consistent with reported data (22,23). Therefore, at the beginning of the cultures most of the cells in the population were reproductively active.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In mammalian cells, the duration of the S phase is almost always 8-10 hr. If all the cells in these young cultures were growing, this would imply a generation (intermitotic) time of between 1 and 4 days, which is consistent with reported data (22,23). Therefore, at the beginning of the cultures most of the cells in the population were reproductively active.…”
Section: Discussionsupporting
confidence: 87%
“…The kinetic difference between the normal cultures and the cultures from the Werner syndrome patients was not due to a difference in the cell-plating efficiency (22).…”
Section: Discussionmentioning
confidence: 84%
“…Thus, phosphorylation of several phosphotyrosine- (15). We have shown here that WF-1 fibroblasts derived from a Japanese patient exhibit a prolonged doubling time and reduced life span as has been seen in other Werner's fibroblasts (14). Furthermore, our analysis revealed significant difference in protein phosphorylation patterns of normal and Werner's fibroblasts.…”
Section: Mitogen-mediatedsupporting
confidence: 65%
“…Fibroblasts from patients with Werner's syndrome usually show a prolonged doubling time and reduced life span (14). Studies including cocultivation and cell fusion of normal and Werner's fibroblasts showed no evidence for complementation between these cells (14).…”
Section: Mitogen-mediatedmentioning
confidence: 99%
“…1 There is much debate on whether organismal aging and cellular senescence may share common pathways. 8,9 In support of this connection, WS derived cells have a diminished lifespan and exhibit signs of accelerated senescence in culture, 10 while immortalized cells exhibit elevated levels of WRN relative to mortal cells. 11 This observation prompted us to investigate a possible role for WRN in the replication potential of cells following oncogenic stimulation.…”
Section: Organismal Senescence and Recq Helicasesmentioning
confidence: 90%